Type 1 protease resistant prion protein and valine homozygosity at codon 129 of PRNP identify a subtype of sporadic Creutzfeldt-Jakob disease. Issue 5 (1st November 1999) - Worrall, Bradford B; Herman, Susan T; Capellari, Sabina; Lynch, Timothy; Chin, Steven; Gambetti, Pierluigi; Parchi, Piero
Abstract : A man was studied with sporadic Creutzfeldt-Jakob disease (sCJD) who had serial cortical syndromes evolving over 15 months without significant ataxia, prominent myoclonus, or periodic complexes on EEG examinations. This clinical phenotype correlated with a predominantly cortical and striatal distribution of lesions and accumulation of protease resistant prion protein with relative sparing of the brainstem or cerebellum. No amyloid plaques were seen and prion protein (PrP) immunohistochemistry only demonstrated very faint granular deposits in the cerebral cortex. Molecular analysis showed homozygosity for valine at codon 129 in the prion protein gene ( PRNP ) and protease resistant prion protein type 1 deposition. The comparison of molecular and clinicopathological features of the present case with those previously reported in sCJD, indicates that valine homozygosity at codon 129 and type 1 protease resistant prion protein are associated with a distinct phenotypic variant of sCJD. The data also support the view that the PRNP codon 129 polymorphism and the physicochemical properties of the protease resistant prion protein are major determinants of phenotypic variability in sCJD.